Influence of CME-diesel blends on the performance and emissions of a light duty automotive common rail direct injection engine - Mercado, Jose Gabriel E.; Quiros, Edwin N. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
The Philippines Biofuels Act of 2006 was established to develop and strengthen the use of local sustainable fuels, particularly biofuels. For biodiesel, as of 2015, only 2% of biodiesel blend is required, with only few studies to prove the effectiveness of the increase in percentage. This study investigates the influence of various Coconut Methyl Ester (CME) Biodiesel blends in a hght duty automotive CRDi engine without any engine modifications through evaluation of engine performance parameters and emission characteristics. Six fuel blends - BO (Neat), B2 (2% CME, 98% B0), B5 (5% CME, 95%B0), BIO (10% CME, 90% B0), B15 (15% CME, 85% B0) and B20 (20% CME, 80% BO) were used. The tests are carried out at 100% and 50% load with varying speeds from 800 to 4000 RPM at an interval of 400 RPM. At typical engine speed range (1200 - 2400 RPM) for both loading conditions, no significant differences for biodiesel blends vs neat diesel were observed for torque, power, and CO2 and NOx emissions. However, a decrease of 1.49% - 44.61% in HC and 0.9% - 20.7% in CO were observed. Meanwhile, at 2800-4000 RPM, an increase of 2.63% - 49.82% in torque and power was observed. There was also an increase of 2.5% - 32.2% in CO2 and 1.04% - 28.99% in NOx, but no significant differences in HC and CO emissions. However, the engine does not normally run at the higher speed range for a long period of time. With respect to biodiesel blends, torque, power, CO2, and NOx emissions generally increased with increasing biodiesel blend, while CO and HC emissions generally decreased with increasing biodiesel blend.
Thesis (M.S. in Mechanical Engineering)--University of the Philippines Diliman
Keywords: Biodiesel fuels; Coconut oil as fuel; Automobiles -- Performance